The Effect of Solar Panel Efficiency Due to Temperature Changes Using Halogen Lamps on Polycrystalline Type Solar Modules - Samsurizal, Samsurizal; Makkulau, Andi; Fikri, Miftahul; Afrianda, Rio (Politeknik Negeri Semarang, 2023)
Solar panels are a technology that utilizes solar energy to be converted into electrical energy. Solar panel technology can be used to generate electricity on a small scale to a large scale. The performance of solar panels depends on environmental factors, namely solar radiation, and temperature. Environmental factors will reduce the electrical efficiency of solar panels due to the increase in operating temperature of solar panels, the greater the temperature will affect their efficiency. Based on tests conducted on photovoltaic (PV) using halogen with different power, the greater the power value in halogen lamp light, the smaller the efficiency, while the greater the temperature of the solar module, the smaller the efficiency. The greater the increase in temperature, the PV efficiency tends to decrease. Based on the results of the study, it shows a significant correlation that, between PV surface temperature and PV efficiency is inversely proportional. While the effect of temperature on efficiency can be said to be quite influential, where in testing with a 300-watt halogen lamp the error rate or R value is 0.6339, while the 500-watt halogen R value is 0.8493 which means it is more accurate and the effect is quite strong.